2003
DOI: 10.1046/j.0043-1737.2003.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inter‐row hoeing and fertilizer placement on weed growth and yield of winter wheat

Abstract: Inter-row hoeing is known to control tap-rooted and erect weed species more effectively in winter wheat than weed harrowing. However, little is known about its effectiveness for use in the spring in winter wheat grown at wide row spacing (240 mm) under the influence of different placement of fertilizer. Two field experiments, one in 1999 and one in 2000, were conducted to study the influence of fertilizer placement, timing of inter-row hoeing, and driving speed on the weeding effect on different weed species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 17 publications
3
56
0
Order By: Relevance
“…At a tractor driving speed of 6 km·h −1 , the yield for the NTS treatment was lower, with an average of 9 t·ha −1 . Treatments GFS (4) and DSK showed similar high results of 9.5 and 9.2 t·ha −1 , respectively. Manual weed removal recorded an average grain yield of 9.7 t·ha −1 .…”
Section: Results At Kleinhohenheimsupporting
confidence: 54%
See 2 more Smart Citations
“…At a tractor driving speed of 6 km·h −1 , the yield for the NTS treatment was lower, with an average of 9 t·ha −1 . Treatments GFS (4) and DSK showed similar high results of 9.5 and 9.2 t·ha −1 , respectively. Manual weed removal recorded an average grain yield of 9.7 t·ha −1 .…”
Section: Results At Kleinhohenheimsupporting
confidence: 54%
“…Moreover, narrowly seeded cereals can better suppress weed infestation compared to wider sowing [7][8][9]. This emphasizes the need to develop new hoeing systems for narrowly spaced cereal systems [4]. Row widths below 200 mm demand adjusted weeding blades and steering technologies to fit into the narrow row spaces and to guide the blades between the crop rows [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined weed survival after hoeing depending on fertilization, with variable results. For example, Melander et al (2002) obtained higher yield of winter wheat when nitrogen fertilizer was incorporated into soil, but no effect on weeds surviving hoeing. Rasmussen (2002) studied the effect of weed control depending on slurry application strategy to spring cereals and found that both mechanical and chemical weed control were more efficient if the slurry was injected rather than surface-applied.…”
Section: Absence Of Weed Hoeingmentioning
confidence: 99%
“…Weed control efficacies were slightly higher than in the studies by Dierauer and Stöppler-Zimmer [21], and almost equal to chemical weed control strategies. Melander et al [29] suggested that hoeing at higher speed could increase soil coverage of intra-row weeds and thus may lead to higher weed suppression. We could prove this hypothesis in our study.…”
Section: Weed Densitymentioning
confidence: 99%